2014
DOI: 10.1186/1472-6874-14-76
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and emotional social support among women who are denied or receive abortions in the United States: a prospective cohort study

Abstract: BackgroundExamining women’s stress and social support following denial and receipt of abortion furthers understanding of the effects of unwanted childbearing and abortion on women’s well-being. This study investigated perceived stress and emotional social support over time among women who were denied wanted abortions and who received abortions, and compared outcomes between the groups.MethodsThe Turnaway Study is a prospective cohort study of women who sought abortions at 30 abortion facilities across the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 52 publications
1
42
1
2
Order By: Relevance
“…A negative correlation was determined between negative emotional problems and emotional social support after abortion . In a study by Harris, the stress experienced by women who underwent therapeutic abortion was higher than women who had a first‐trimester abortion, and this stress was higher in women who refused a therapeutic abortion.…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation was determined between negative emotional problems and emotional social support after abortion . In a study by Harris, the stress experienced by women who underwent therapeutic abortion was higher than women who had a first‐trimester abortion, and this stress was higher in women who refused a therapeutic abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Also, most women in the Near Limit group received terminations later in gestation than most US women (Pazol et al, 2013). However, our previously published analyses of alcohol, tobacco, drug use, stress, mental health, and emotions found that Near Limits are substantially similar to First Trimesters in their experiences subsequent to the termination (Foster et al, 2015; Harris et al, 2014; Roberts et al, 2015; Roberts and Foster, 2015; Roberts et al, 2014c; Rocca et al, 2015). We also note that about 10% of Turnaway Births placed their babies for adoption.…”
Section: Discussionmentioning
confidence: 93%
“…The Turnaway Study seeks to understand how the outcome of an unwanted pregnancy affects women’s subsequent physical and mental health and socioeconomic status (Foster et al, 2015; Harris et al, 2014; Roberts et al, 2014a, 2015; Roberts and Foster, 2015; Roberts et al, 2014c; Rocca et al, 2013, 2015). Analyses presenting the main effects of termination vs. birth on subsequent alcohol use, binge drinking, and problem symptoms have been published previously (Roberts et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations